2017
DOI: 10.1007/s10151-017-1701-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an online risk calculator for the prediction of anastomotic leak after colon cancer surgery and preliminary exploration of artificial intelligence-based analytics

Abstract: The anastomotic leak risk calculator is significantly predictive of anastomotic leak after colon cancer resection. Wider investigation of artificial intelligence-based analytics for risk prediction is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…Previous studies have reported on data collected during the ANACO project: one study used as an end‐point the risk of leakage in all types of colonic resections , from which an online calculator has been developed and validated ; another study reported on factors associated with complications after right colectomy . Left colectomies without diversion ileostomy need separate assessment due to the anatomical and technical issues associated with left‐sided colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported on data collected during the ANACO project: one study used as an end‐point the risk of leakage in all types of colonic resections , from which an online calculator has been developed and validated ; another study reported on factors associated with complications after right colectomy . Left colectomies without diversion ileostomy need separate assessment due to the anatomical and technical issues associated with left‐sided colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation was not significantly higher after stent placement (3.1% vs 4.8%, no stent vs stent, P = 0.48). The median number of nodes isolated from the specimen was 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Pathology and Perioperative Outcomementioning
confidence: 99%
“…The accuracy of CLS was initially reported to be quite high [AUROC, 0.95 (95% CI, 0.89–1.00)] [31]. Two studies performed subsequently to validate the CLS gave relatively good results, with the AUROC being 0.965 (95% CI, 0.913–1.00) and 0.80 (95% CI, 0.618–0.982) [32,33]. In this study, although the mean CLS was significantly higher in the AL group than in the No Leakage group, the predictive strength of CLS (AUROC 0.701) was not as high as was anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the comparison using ROC curves, we were able to confirm that the newly developed AL classifier (m-CLS) has a better predictive power than the CLS. Several AL risk prediction models have been developed for patients with colorectal cancer [33,47,48,49,50]. These predictive models would ultimately help surgeons decide whether to perform a diversion indirectly, by estimating a possibility of AL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation